A study of depth structure of the earth crust at the Antarctica coast by a geopolariton sounding technique - Bogdanov, Yu. A.; Zakharov, I. G.; Vashchenko, V. M.; Pavlovych, V. M. (Ukrainian Antarctic Journal, 2006)
The results of a preliminary interpretation of the measurements at the Antarctic coast by a geopolariton sounding technique are presented. The technique allows to obtain an information about the strained and deformed state of the rocks. The measurements are carried out in 2005-2006 on a glacier at Galindez Island and at the ships of the X-XI Ukrainian Antarctic Expedition along the continent coast from the Akademik Vernadsky Station up to South Shetland Islands and through the Dreyk Strait.